PENGARUH KUALITAS PELAYANAN DAN KEPUASAN WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK KENDARAAN BERMOTOR (Studi Pada Kantor Bersama Sistem Administrasi Manunggal di Bawah Satu Atap (SAMSAT) Kendari) - Awaluddin, Ishak; Nurnaluri, Sitti; Damayanti, Wa Ode Rahmi (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
ABSTRACTThe aim of this research is to test the effect of service quality and tax payerâs satisfaction to the obedience of paying motorized vehicle tax in the Kendari office of one roof system. The data collection technique used in this research is documentation and questionnaires. The samples used in this research is 98 compulsory motorized vehicle tax that is registered in Kendari office of one roof system. The analysis method used is multiple linear regression.The result of this research is to show that service quality affects significantly to the obedience of paying motorized vehicle tax. This statement is supported by the first hypothesis test result, which is (thitung = 4,294> ttabel = 1,661 ) or with the significant degree of 0,000 < Î± = 0,05, so that H1 is accepted, thus, service quality affects significantly partially to the obedience of paying motorized vehicle tax. It is because the service location of paying motorized vehicle tax is qualified enough along with the efficient and friendly one roof systemâs officer at serving the tax payers. It means that the better the service quality given to the tax payers in the office of one roof system, the higher the obedience of tax payers at paying the motorized vehicle tax. The tax payerâs satisfaction affects positively but not significant to the obedience of paying motorized vehicle tax. The result of the second hypothesis, which is (thitung = 1,788 < ttabel= 1,661) or with the significant value of 0,077 > Î± = 0,05, which means that the tax payerâs satisfaction affects positively but not significant partially to the obedience of paying motorized vehicle tax. It means that, the tax payerâs satisfaction has given a positive contribution but still not meaningful for improving the obedience of paying motorized vehicle tax. It is because that the tax payersâ think that the simplicity to get explanation about unclear things related to motorized vehicle tax is still not satisfying.Â Keywords : Service quality, tax payerâs satisfaction, the obedience of paying tax